2006
DOI: 10.1029/2005ja011453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of He++ ions on the propagation of low‐frequency magnetohydrodynamic waves in the magnetosheath

Abstract: [1] The paper investigates the role of suprathermal particles (He ++ ) in the propagation of low-frequency waves in average magnetosheath plasma by utilizing a model which is a concatenation of two magnetohydrodynamic (MHD) fluids. The suprathermal component is described by a relativistic, collisionless anisotropic fluid while the background plasma is assumed to be a nonrelativistic, anisotropic MHD fluid. The pressure components of both the fluids are described by heuristic double-polytropic laws which are fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…The wave is governed by the electron dynamics which is assumed to be adiabatic, ensuring an adequately larger time scale compared to the electron plasma frequency of the associated plasma system. On the other hand, ions are assumed to be hotter than the electrons ( ) (Kalra & Kumar 2006) and obey Boltzmann distributions. The spatio-temporal scale of the ions are determined by their Larmor radius and the inverse of the gyrofrequency which are typically much larger than the wavelength and the time period of the electron acoustic wave.…”
Section: The Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave is governed by the electron dynamics which is assumed to be adiabatic, ensuring an adequately larger time scale compared to the electron plasma frequency of the associated plasma system. On the other hand, ions are assumed to be hotter than the electrons ( ) (Kalra & Kumar 2006) and obey Boltzmann distributions. The spatio-temporal scale of the ions are determined by their Larmor radius and the inverse of the gyrofrequency which are typically much larger than the wavelength and the time period of the electron acoustic wave.…”
Section: The Analytical Solutionmentioning
confidence: 99%
“…It is well known that, when the solar wind crosses the bow shock, ions get energized and eventually becomes hotter than electrons (Treumann & Sagdeev 2005; Kalra & Kumar 2006). In such cases, it was found that an electron acoustic mode can be excited in a plasma.…”
Section: Introductionmentioning
confidence: 99%
“…For the major part of the magnetosphere, the plasma consists of multi‐ion species with a minority population of O + ions in the cusp or He +2 ions in the bow shock and magnetosheath. The presence of such minority components may play a crucial role in determining the plasma properties and the wave generation processes [ Kalra and Kumar , 2006]. In our present study, we have assumed a multi‐ion plasma consisting of hydrogen and oxygen ions with single charge multiplicities ( z 1 , z 2 = 1) while α e = 0.5.…”
Section: Electron Acoustic Solitary Wavesmentioning
confidence: 99%
“…We have assumed the bulk (beam) electron temperatures as 35 (28) eV with density ratio 4.9 ( ρ es = 0.98) and eb (nonnormalized electron beam velocity) has been taken to be 650 km/s [ Shin et al , 2006]. Following Kalra and Kumar [2006], we have assumed the existence of the suprathermal particles where ion temperatures lie within 100 eV to 10 keV. We have assumed > and β i = 1/4, the proton temperature being 300 eV.…”
Section: Comparison With Space Observationsmentioning
confidence: 99%
“…34 Ions in the magnetosheath have complex and broad distributions after they penetrated the bow shock. 33,[35][36][37] The He 2+ /H + density ratio in the magnetosheath was, for example, 6.2% ± 0.6% during the magnetopause crossing recorded by MMS4 on 22 November 2015. 29 Temperatures 2+ in the magnetosheath may vary over a quite broad range.…”
Section: Systematic Errors Due To the Presence Of Heavy Ionsmentioning
confidence: 97%